Fingerprinting the painted storks (Mycteria leucocephala pennant), milky storks (Mycteria cinerea raffles) and their suspicious hybrids in a zoo in Malaysia - Yee, Yoke Sim (2017)
Painted storks (Mycteria leucocephala) and milky storks (Mycteria cinerea) are large wading birds of southern Asia, and listed as endangered species by IUCN (International Union for Conservation of Nature). Most painted storks inhabit India while milky storks mainly colonise east Sumatra and the west coast of Peninsular Malaysia. In the past decade, no wild milky stork has settled in Peninsular Malaysia. Both species were captive bred at the Zoo Negara for conservation purposes. Yet, storks with intermediate plumage traits between two stork species were observed, and suspected to be their hybrids. Based on the intermediate plumage characteristics, hybrids of two storks were suspected at natural breeding sites of Cambodia, Singapore, and Thailand. However, mere plumage appearances are often insufficient to confirm the bird hybrids, and hence, molecular markers are used. Unbalanced sex ratio in a population could be one of the reasons that two species hybridised. Females and males of both stork species have no differentiation in plumage traits, and therefore, molecularsexing markers are used to identify genders. The objective of this study was to fingerprint individual storks using different classes of DNA markers including sexlinked marker to identify hybrids, and to estimate sex ratio. Based on the plumage characteristics of each stork, blood was sampled systematically onto FTA cards (Whatman, classic) (FTA – fast analysis of nucleic acids). DNA was extracted from a disc of FTA cards (3 mm), and PCR was run with RAPDs (random amplified polymorphism DNA), ISSRs (inter-specific sequence repeat), and cross species microsatellites, electrophoresed on agarose gels and stained with ethidium bromide. Six out of 44 screened primers were selected to fingerprint each stork, and two distinctive sets of banding patterns were generated, which differentiated pure storks from hybrids. These six markers included two wood stork microsatellites (WSU09U/WSU09L and WSU13U/WSU13L), two short RAPDs (Operon D-03 and Operon D-05), one long RAPD (LR7), and one 5’-anchored ISSR (RAM2). The data revealed that most loci of hybrids were combinations of two pure storks, few loci were exclusively found in hybrids alone. The fingerprinting data were compared to plumage characteristics, and it was found out these hybrids possessed six different types of intermediate plumage characteristics between two parental species, and they were not a typical kind of hybrid only. Sex-linked microsatellites P2/P8 was run with PCR, electrophoresed PCR products on 7.5% PAGE gel (non-denaturing) and stained with silver staining. The result showed that sex ratio of female to male in painted stork population was 1 to 5, while all hybrids and milky storks were males, indicating that males were the majority. It can therefore be concluded that stork hybrids were identified through DNA fingerprinting using six selected DNA markers. The hybrids of intermediate plumage traits were confirmed by DNA fingerprinting. Sex ratio in the breed storks was not balanced.